Foreign debt and financial fragility in the perspective of the emerging countries - Tonveronachi, Mario (PSL Quarterly Review, 2012)
Following the financial fragility approach of H. Minsky and its later extension by J. Kregel, the paper addresses some basic aspects of the dynamics and management of foreign debt in the perspective of the emerging countries. Minsky's definitions of hedge, speculative and Ponzi positions are restated in order to define a country's external fragility. How international asymmetries in the external financial fragility may influence global fragility is then discussed, leading to analyse the limits of financial openness. Finally, the distinction between domestic and external financial fragility permits to look at how the dynamic interplay among the economic units, including the government and its policies, may influence both the distribution and the level of the two types of fragilities. JEL Codes: F21, F32, F34